FOREIGN OWNERSHIP AS A MODERATION VARIABLE IN TAX HEAVEN, TAX MINIMIZATION AND TUNNELING INCENTIVE FOR TRANSFER PRICING - Siregar, Indra Gunawan; AR, Khorida; Rohmansyah, Budi; Putri, Atika Meliana (Universitas Muhammadiyah Tangerang, 2025)
The purpose of this to determine the effect of tax heaven, tax minimization and tunneling incentive on transfer pricing with foreign ownership as a moderation variable in manufacturing companies listed on the Indonesian Stock Exchange (IDX). The research time period used is 5 years, namely the period 2018-2022. The population of this research includes all manufacturing companies listed on the Indonesian Stock Exchange (IDX) for the 2018-2022 period. The sampling technique uses purposive sampling tchnique. Based on the established criteria, 29 companies were obtained. The type of data is secondary data obtained from the Indonesian Stock Exchange website. The analysis method used is Moderate Regression Analysis (MRA) with the help of Eviews 12 software. The results of this research partially show that tax heaven and tax minimization have no effect on transfer pricing. Tunneling incentive have a positive effect on trasnsfer pricing. Foreign ownership has no effect on transfer pricing. Foreign ownership does not moderate the effect of tax heaven on transfer pricing. Foreign ownership is able to moderate the relationship between tax minimization and transfer pricing. Foreign ownership does not moderate the tunneling incentive relationship with transfer pricing. Simultaneous research results show that tax heaven, tax minimization and tunneling incentive have a significant effect on transfer pricing decisions.